Studi Kasus Kesiapan Rumah Sakit Haji Jakarta dalam Antisipasi Bencana Tahun 2021 - Denny Setiawan; Febrianti, Febrianti; Eka Hartomy (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
DKI Jakarta is one of the provinces that is significantly vulnerable to various types of disasters, with flooding being the most frequent and recurring annually. Earthquakes also pose a substantial threat to the residents of DKI Jakarta, given the history of severe seismic events in the past, coupled with the presence of the Baribis fault and the Megathrust. Jakarta Hajj Hospital must prepare its institution to be adequately equipped to address potential disaster threats. This study focuses on assessing the preparedness of Jakarta Hajj Hospital in managing disasters. The objective of this research was to determine the readiness of the Jakarta Hajj Hospital in anticipating disasters in 2021. This study employed a descriptive qualitative research methodology with explorative study design. The data utilized comprise primary data obtained through in-depth interviews and observations, as well as secondary data derived from documentation and guidelines of the Jakarta Hajj Hospital. The analysis employed an interactive model from Miles and Huberman. Based on the results and discussion of the research, it can be concluded that out of the four standards considered—management, human resources, buildings, and cooperation—which encompass a total of 50 indicators across 11 existing parameters, only 9 indicators do not conform to the Disaster Safe Hospital Standards. This indicates that the Jakarta Hajj Hospital demonstrates a relatively high level of preparedness.